Answer:
Reflection across y axis
Translate up by 3 units
Step-by-step explanation:
Given
![f(x) = x + 1](https://tex.z-dn.net/?f=f%28x%29%20%3D%20x%20%2B%201)
![g(x) = -x + 4](https://tex.z-dn.net/?f=g%28x%29%20%3D%20-x%20%2B%204)
Required
Describe the transformation from f(x) to g(x)
First, take a reflection of f(x) across the y axis.
So f(x) becomes f(-x)
when reflected
![f(-x) = -x +1](https://tex.z-dn.net/?f=f%28-x%29%20%3D%20-x%20%2B1)
Next, translate f(-x) up by 3 units to give g(x)
![g(x) = f(-x) + k](https://tex.z-dn.net/?f=g%28x%29%20%3D%20f%28-x%29%20%2B%20k)
Where
![k = 3](https://tex.z-dn.net/?f=k%20%3D%203)
![f(-x) = -x +1](https://tex.z-dn.net/?f=f%28-x%29%20%3D%20-x%20%2B1)
![g(x) = -x + 1 + 3](https://tex.z-dn.net/?f=g%28x%29%20%3D%20-x%20%2B%201%20%2B%203)
![g(x) = -x + 4](https://tex.z-dn.net/?f=g%28x%29%20%3D%20-x%20%2B%204)
Hence, the transformation from f(x) to g(x) includes:
Reflection across y axis
Translate up by 3 units
Answer:
A. 15
Step-by-step explanation:
Width (w): 5
Height (h): 6
Area of Triangle (A) = 1/2wh
A = 1/2(5)(6)
A = 5 x 3
A = 15 units squared
Hope this helped! <3
Answer:
60
Step-by-step explanation:
rate of change of graph,df(x)/dx
=(120-0)/(3-1)=60
Answer:
0.318
Step-by-step explanation: